(untitled) (Journal of Nobel Medical College, 2025)
Background: A focused computed tomography scan serves as a critical diagnostic modality for acute appendicitis, particularly in instances where clinical findings are equivocal or ultrasound results lack clarity. This study was carried out to assess the diagnostic accuracy of Focused Appendiceal Computed Tomography as a viable alternative to the conventional Computed Tomography of the abdomen and pelvis in patients suspected of having acute appendicitis. Materials and Methods: Prospective cross sectional study of 100 adults were performed with suspected acute appendicitis. Each patient underwent a Computed Tomography of the abdomen and pelvis with both oral and intravenous contrast. A subset of axial images, ranging from the top of the L4 vertebral body to the roof of the acetabula, was extracted from each scan to create the Focused Appendiceal Computed Tomography. After reviewing the focused Appendiceal Computed Tomography images, the conventionalComputed Tomography of the abdomen and pelvis scans were also evaluated, with each patient serving as their own control. The images were analyzed to determine their ability to identify the appendix, diagnose appendicitis, or detect alternative conditions that could explain the presenting symptoms. Results: Out of 100 cases, the appendix was visible in the Focused Appendiceal Computed Tomography scans of 92 patients. In 8 cases, the appendix could not be visualized in either the focused or standard Computed Tomography of the abdomen and pelvis scans.Out of the 100 cases scanned,63 cases were abnormal and 37 cases were normal. Among 63 abnormal cases, Focused Appendiceal Computed Tomography identified 42 cases of acute appendicitis, which was consistent with the findings from the standard Computed Tomography of the abdomen and pelvis. Additionally, 21 patients were found to have alternative diagnoses. Conclusion: In this study Focused Appendiceal Computed Tomography provided identical diagnostic results. There is no difference in performance between Focused Appendiceal Computed Tomography and Conventional Computed Tomography of abdomen and pelvis in diagnosing of acute appendicitis in this study.